Analisis Kinerja Keuangan Dengan Metode Economic Value Addes (EVA) Pada PT. Indofood Sukses Makmur Tbk. Tahun 2018-2022 - Wenseslaus Lakonawa; Nugraeni Nugraeni (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
One way that shareholders might evaluate financial performance is by looking at Economic Value Added (EVA). Economic Value Added (EVA) is a tool that this study intends to use to examine PT Indofood Sukses Makmur Tbk's financial performance. This study employs a quantitative approach to descriptive research. With PT Indofood Sukses Makmur Tbk as the study's subject. The quantitative data used in this study was gathered from secondary sources, including the IDX website and the yearly financial statements of PT Indofood Sukses Makmur Tbk for the years 2018–2022. Based on the data, it seems that PT Indofood Sukses Makmur Tbk. had respectable, although variable, financial success from 2018 to 2022 as measured using the Econoimic Value Added (EVA) technique. An EVA result that is positive indicates this. A good EVA shows that PTIndofood Sukses Makmur Tbk. is able to provide economical added value, the firm operates effectively, and the prosperity of shareholders grows; nonetheless, the company did achieve a negative EVA in 2022.